Bridging the digital divide for sustainable agriculture: how digital adoption strengthens farmer livelihood resilience - Lyu, Zicheng; Jing, Zaifang; Yang, Xiaoli (Frontiers in Sustainable Food Systems, 2025)
IntroductionAgricultural systems worldwide face intensifying pressures from climate change, market volatility, and resource degradation, making farmer livelihood resilience—the capacity to maintain and adapt livelihood strategies under disturbances—crucial for sustainable development. This study examines how digital technology adoption affects farmer livelihood resilience in China's evolving agricultural landscape.MethodsWe surveyed 1,395 grape farmers in Liaoning Province, China, employing a multi-stage stratified random sampling approach. Using econometric methods within a sustainable livelihoods framework, we analyzed digital adoption across three dimensions (production, sales, and financial services) and its impact on five livelihood capital types (financial, physical, natural, human, and social capital). Instrumental variable approaches addressed potential endogeneity concerns.ResultsDigital adoption significantly enhanced farmer livelihood resilience, with digital sales adoption showing the strongest effect, followed by production and financial services adoption. Two key mechanisms emerged: enhanced signal reception capabilities that improve market information acquisition, and strengthened signal transmission capabilities that enable farmers to demonstrate credibility to external stakeholders. Heterogeneity analysis revealed that low-to-middle income farmers experienced greater marginal benefits, with effects diminishing at higher income levels and becoming insignificant for the highest income group.DiscussionWhile demonstrating digital technology's potential for inclusive rural development, critical challenges persist. Infrastructure requirements may exclude vulnerable groups, data extraction by platforms raises sovereignty concerns, and rapid digitalization risks eroding traditional knowledge systems. These tensions necessitate policy interventions ensuring equitable access, protecting farmer agency in data governance, and balancing technological innovation with cultural preservation.